STUDI LITERATUR TENTANG KONSEP DIRI REMAJA - Elvina Ningsih; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Asbract: This study was conducted to determine the theoretical concept of Self-Concept,factors that influence Self-Concept, and Efforts to improve Adolescent Self-Concept. This typeof research used is literature study. The instrument used in this research is a combination ofnational journals and international journals. Data analysis in this study used qualitativeanalysis methods. The results showed that the self-concept is an individual's view or perceptionof himself, which can reflect how the individual's behavior is in accordance with the selfconcepthe has. The relevant theory from the findings of this study is the looking glass selftheoryproposed by Charles Horton Cooley. This theory says that self-concept is like walking ina mirror. Individuals see what is reflected. The results of the research on the factors thatinfluence the Adolescent Self-Concept have a greater influence on environmental factors (peerfactors). While the results of research on ways to improve Adolescent Self-Concept in the formof efforts that can be done by teachers in the school environment, such as Cognitive BehaviorGroup Counseling, Narrative counseling, extracurricular pencat silat, REBT approaches, andsupport and motivation of teachers and parents.Key Words: Study Literatur, Adolescent, Self-Concepts